Bitemporal Postoperative Hemorrhage Following Pterional Craniotomy for the Treatment of an Internal Carotid Aneurysm - Welling, Leonardo; Welling, Mariana; Figueiredo, Eberval Gadelha (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2017)
Introduction Postoperative hemorrhage is a well-known complication after intracranial surgeries. It usually occurs at the site of the operation; however, there are many reports of cerebellar hemorrhage following supratentorial craniotomies. Despite that, there are only three cases of multiple postoperative supratentorial hemorrhages (distant from the site of the operation) following aneurysm clipping in the current literature.Case Report A 52-year-old previously healthy woman underwent a left pterional craniotomy for the clipping of an unruptured aneurysm. The surgery was performed without any intraoperative rupture or other occurrences. On the follow-up computed tomography (CT) scan performed 24h after surgery, bilateral posterior temporal lobe hematomas were identified, and they had no relation to the surgical site. The patient developed symptomatic vasospasm, with right-sided hemiparesis. This complication was treated conservatively, and the outcome was good.Conclusions Intracerebral hemorrhage far from the site of the craniotomy is an infrequent complication after neurosurgical procedures, especially in vascular neurosurgery. The present report warns of the occurrence of this entity even in asymptomatic patients.
Keywords: cerebral aneurysm; hemorrhage; postoperative period